2020
DOI: 10.4314/ijbcs.v14i2.10
|View full text |Cite
|
Sign up to set email alerts
|

Variabilité des traits fonctionnels des espèces arborescentes dans la reconstitution de la végétation du Parc National d’Azagny (Côte d’Ivoire)

Abstract: Dans le Parc National d’Azagny, des plantations de cultures pérennes ont été abandonnées, certaines détruites de même que des habitats successivement en 1986 et 2000. Ainsi donc, l’ensemble de la végétation du parc est constitué de reliques de forêts anciennes, de forêts secondaires et de jachères d’âge différents. La présente étude a évalué les changements des traits fonctionnels des espèces végétales arborescentes dans différentes formations du Parc National d’Azagny. Il s’est agi, spécifiquement de : décrir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(17 reference statements)
1
0
0
Order By: Relevance
“…However, the spectrum of diaspore types in this forest reveals the predominance of plants with drupaceous fruits or arillate seeds. These results are similar to those of some predecessors [ 57 , 64 , 68 ] who have shown that a significant number of animals depend on fleshy-fruited species for their food. As a result of the disturbances noted, a fairly high proportion of pterochorous taxa (on average 0.97%) was noted in the logged forest.…”
Section: Discussionsupporting
confidence: 91%
“…However, the spectrum of diaspore types in this forest reveals the predominance of plants with drupaceous fruits or arillate seeds. These results are similar to those of some predecessors [ 57 , 64 , 68 ] who have shown that a significant number of animals depend on fleshy-fruited species for their food. As a result of the disturbances noted, a fairly high proportion of pterochorous taxa (on average 0.97%) was noted in the logged forest.…”
Section: Discussionsupporting
confidence: 91%